3D Polyaniline architecture by concurrent inorganic and organic acid doping for superior and robust high rate supercapacitor performance - Gawli, Yogesh; Banerjee, Abhik; Dhakras, Dipti; Deo, Meenal S.; Bulani, Dinesh; Wadgaonkar, Prakash P.; Shelke, Manjusha; Ogale, Satishchandra (Scientific Reports, 2016)

Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.

Ice-colloidal templated carbon host for highly efficient, dendrite free Li metal anode - Patrike, Apurva; Kaniyamparambil, Karthika; Wahid, Malik; Chaturvedi, Vikash; Shelke, Manjusha (Carbon, 2021)
With its high theoretical specific capacity value, lithium metal itself would be an ideal anode material for rechargeable Li-ion batteries (LIBs). However, practical application of lithium metal is obstructed due to lithium dendrite growth during cycling leads to unstable SEI formation, volume fluctuation and safety hazard. Herein, we have developed a novel high surface area carbon network with both meso (∼20 nm) and micron (∼1–2 μm) size porosity, via ice-colloidal templating, as a scaffold for stable lithium metal anode mitigating lithium dendrite formation. The 3D porous nitrogen doped carbon (3D PNC) network is capable of lithium deposition equivalent to 10 mAhcm−2 at 2 mAcm−2 current density with 99.96% coulombic efficiency for 100 cycles. Moreover, 3D PNC when subjected to 3000 h of continuous plating-stripping measurements (∼700 cycles) depicts the coulombic efficiency of 99.84% with no observable dendrite growth at the current density of 2 mAcm−2 and lithium intake capacity of 5 mAhcm−2. A full cell of lithium plated 3D PNC anode with LiFePO4 shows an excellently stable performance up to 50 cycles at an input current density of 50 mAg−1, with a coulombic efficiency retention of 99.73%.

Research progress and perspective on lithium/sodium metal anodes for next-generation rechargeable batteries - Patrike, Apurva; Yadav, Poonam; Shelke, Vilas; Shelke, Manjusha (ChemSusChem, 2022)
With the development of consumer electronic devices and electric vehicles, lithium-ion batteries (LIBs) are vital components for high energy storage with great impact on our modern life. However, LIBs still cannot meet all the essential demands of rapidly growing new industries. In pursuance of higher energy requirement, metal batteries (MBs) are the next-generation high-energy-density devices. Li/Na metals are considered as an ideal anode for high-energy batteries due to extremely high theoretical specific capacity (3860 and 1165 mAh g(-1) for Li and Na, respectively) and low electrochemical potential (-3.04 V for Li and -2.71 V for Na vs. standard hydrogen electrode). Unfortunately, uncontrolled dendrite growth, high reactivity, and infinite volume change induce severe safety concerns and poor cycle efficiency during their application. Consequently, MBs are far from commercialization stage. This Review represents a comprehensive overview of failure mechanism of lithium/sodium metal anode and its progress for rechargeable batteries through (i) electrolyte optimization, (ii) artificial solid-electrolyte interphase (SEI) layer formation, and (iii) nanoengineering at materials level in current collector, anode, and host. The challenges in current MBs research and potential applications of lithium/sodium metal anodes are also outlined and summarized.
Keywords: anode; Batteries; dendrite growth; Electrolytes; Energy storage

Role of 2D material families in energy harvesting: an editorial overview - Raghavan, Prasanth; Ahn, Jou-Hyeon; Shelke, Manjusha (Journal of Materials Research, 2022)
The ever increasing proportion of an energy consuming society and the boost in industrialization accelerated the depletion of fossil fuel based energy sources at an alarming rate. This emphasizes the necessity of sustainable energy generation and storage to meet the daily energy demands. But, these alternative renewable energy sources like solar and wind power are intermittent and highly depend on weather, place and individuals. This creates the inevitability of suitable energy storage devices like batteries and supercapacitors. The interfacing of energy storing devices is required to maintain the supply chain equilibrium, power efficiency, regulate power fluctuations and reduce pollution. Besides, the boom in electric mobility and consumer electronics also require uninterrupted power supply. Hence, in the upcoming years the energy storing devices play a vital role in addressing the energy crisis. Innovations in new materials and technologies will be the core area of research and development in the coming future. 2D materials like graphene,transition metal carbides and nitrides (MXenes), transition metal borides (MBenes) and so on are the new class of materials among them MXenes are getting more attention in energy storage owing to its exceptional properties.

Benign strategy toward mesoporous carbon coated Sb nanoparticles: a high-performance Li-ion/Na-ion batteries anode - Dashairya, Love; Chaturvedi, Vikash; Kumar, Abhishek; Mohanta, Tandra Rani; Shelke, Manjusha; Saha, Partha (Solid State Ionics, 2023)
Antimony (Sb)-based anodes can offer excellent gravimetric capacity (-660 mAhg(1)) in lithium-ion/sodium-ion batteries (LIBs/SIBs) fabricated using carbonate-based electrolytes complexed with lithium/sodium salt. However, high first-cycle irreversible loss (35-40%) and gradual capacity fade (25-30%/cycle) originate from solid electrolyte interphase (SEI), and severe volumetric stress (-300%) associated with alloyed phase(s) impede reallife applications. Herein, we devise a benign strategy to develop mesoporous carbon coating onto antimony nanoparticles (Sb@C) based core-shell architecture for LIBs/SIBs anode. In particular, -30-50 nm thick mesoporous carbon spheres (-1 +/- 0.5 mu m) were obtained from resorcinol-formaldehyde (RF)-based polycondensation reaction by sol-gel chemistry engulfing Sb nanoparticles by suitably controlling Cetyltrimethylammonium bromide (CTAB)-induced steric stabilization and pH modulation during synthesis. The core-shell Sb@C helps faster Li+/Na+-ion migration preventing the structural collapse of Sb during electrochemical cycling and thereby improving the capacity fade. Electrochemical results demonstrate Sb@C can deliver a specific capacity of -536 mAhg(-1) and - 291 mAhg(-1) at 0.1C current rate in LIBs and SIBs, respectively, up to 200 cycles. Electrochemical impedance spectroscopy (EIS) indicates lower charge transfer (Rct) and SEI resistance (RSEI) of Sb@C cycled electrode than the bare Sb-NPs was the probable reason for improved Li/Na-ion storage in Sb@C anode. A detailed galvanostatic intermittent titration technique (GITT) and internal resistance measurements during 1st and 2nd cycles shed light on distinguishably different Li-ion/Na-ion storage behavior. The bulk Li+/Na+-ion diffusion coefficients found diminishes at reaction voltages (0.9 V/0.6 V for lithiation and 0.6 V/0.4 V for sodiation) corresponding with alloyed phase(s) concurrent with a drop in internal resistance at the quasi-opencircuit voltage (QOCV) during 1st and 2nd discharge cycle. On the contrary, de-alloying phenomena from the fully lithiated/sodiated phase(s) display an entirely opposite trend. The Li+ diffusion coefficient reaches minima at -1.1 V with a sudden jump in the internal resistance at QOCV during 1st and 2nd charge cycle. However, Na+ diffusion coefficient gradually drops along with a steep increase in the internal resistance, indicating partial Naion trapping and irreversible capacity loss.
Keywords: anode; Antimony; lithium-ion batteries; mesoporous carbon; Sodium-ion batteries

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides

Safety enhanced novel polymer electrolytes for lithium-ion battery: Anomalous output performance with long term cycling stability by doping and polymer blending - Balakrishnan, Neethu T. M.; Melepurakkal, Amrutha; Das, Akhila; Kenz, K. T. Mohammed; Subramaniam, Mohanapriya; Shelke, Manjusha; Pullanchiyodan, Abhilash; Raghavan, Prasanth (MATERIALS TODAY CHEMISTRY, 2024)
Keywords: Blend polymers; Ceramic fillers; Gel polymer electrolytes

Wide temperature enhanced sodium storage in tailored, sustainable sodiophilic biphasic N-doped carbon - Yadav, Poonam; Das, Anoushka K.; Torris, Arun; Wasnik, Kundan; Koppisetti, Heramba Venkata Sai Rama Murthy; Pol, Vilas G.; Shelke, Vilas; Shelke, Manjusha (Materials Today Chemistry, 2024)
Alternative to Li-ion batteries(LIB), Na-ion batteries (NIB) and Na metal batteries (NMB) are gaining significant attention due to their low cost, abundance, and safety. By modulating microstructural properties such as graphitization, heteroatom doping, surface-rich functional groups, and interlayer d-spacing, Na-ion storage in NIB and Na plating/striping in NMB can be ameliorated. This study reports sodiophilic N-doped polymer-derived carbon (PDC) as an anode for NIB and host for Na metal in NMB. As NIB anode, PDC provides a storage capacity of 173 mAh g- 1 at 1 A g- 1 in half-cell and 84 mAh g- 1 at 1C (1C = 128 mAhg- 1) in full-cell with Na3V2(PO4)2F3 (NVPF) cathode. As Na metal anode (NMA) host, a high columbic efficiency (C.E.) of 99.45% for over 1000 cycles at 6 mA cm- 2_4 mAh cm-2 is obtained. Furthermore, fascinating wide temperature (50 degrees C and -20 degrees C) sodiumion storage is successfully demonstrated by PDC. Advanced X-ray photoelectron spectroscopy (XPS) confirmed the formation of stable and uniform solid electrolyte interphase (SEI) composed of inorganic and organic components, X-ray microtomography confirmed uniform Na plating throughout the volume of the electrode analogous to Brunauer-Emmett-Teller (BET) surface area, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) results. A sustainable and scalable promising biphasic NIB anode and sodiophilic host for Na metal was possible due to larger d-spacing, partial graphitization, high mesoporosity, N-doping, presence of surface functional groups, better charge transfer, and diffusion properties.
Keywords: Full-cell; Low and elevated temperatures; Na metal host; Polymer-derived carbon; Sodium-ion battery; X-ray tomography

A carbon nanotube wrapped Na3V2(PO4)2F3 cathode with a dual cation electrolyte: enhancing high-voltage stability and cyclability in zinc-ion batteries - Pandey, Priyanshi; Shivade, Rajkiran; Deshmukh, Ashvini; Shelke, Manjusha (Nanoscale, 2025)
Aqueous zinc-ion batteries (ZIBs) offer several compelling advantages as a safer and sustainable energy storage system. Polyanion-based cathodes, characterized by their comparatively higher voltage and structural stability, are promising for ZIBs. However, challenges hinder their practical applications, such as inferior rate capability and limited cycling stability. In this study, we constructed a carbon nanotube wrapped Na3V2(PO4)2F3 (NVPF-CNT) cathode integrated with a highly concentrated dual cation electrolyte (DCE) to enhance the electrochemical performance of ZIBs by enabling a synergistic Na+ and Zn2+ co-insertion mechanism. The DCE effectively regulates the solvation structure, stabilizes the solid electrolyte interface (SEI), minimizes free water molecules, thereby widening the electrochemical window and reducing the side reactions, and inhibits cathode dissolution. Consequently, the CNT-wrapped NVPF cathode exhibits an initial reversible capacity of 131.3 mAh g-1 at 0.05 A g-1, and retains 84% of its capacity over 500 cycles at 1 A g-1, with a nominal voltage of similar to 1.5 V. This approach offers valuable insights into the potential of CNT-wrapped NVPF cathodes in combination with a DCE while providing a comprehensive framework for advancing high-performance ZIBs.

Insights into electrolyte-solvent interactions and SEI formation for sustainable sodium-ion battery operation at low temperatures - Kim, Soohwan; Mirzapure, Vinay; Atwi, Rasha; Koppisetti, Heramba V. S. R. M.; Wasnik, Kundan; Rajput, Nav Nidhi; Shelke, Manjusha; Pol, Vilas G. (Small Methods, 2025)
Sodium-ion batteries (SIBs) show promise as an alternative to lithium-ion batteries. However, they face performance challenges at ultra-low temperatures (<-40 degrees C) due to slow Na+ transfer kinetics with conventional electrolytes. This limitation restricts their use in extreme environments such as polar regions and outer space. The presented systematic study addresses this challenge by modulating and tailoring the electrolyte composition for SIBs, enabling ultra-low temperature operation down to -110 degrees C for the first time. The comprehensive molecular dynamic and density functional theory calculations combined with experimental Raman spectroscopy and nuclear magnetic resonance studies of advanced electrolytes provided a deeper mechanistic understanding of the solvation structures and their impact on electrochemical performance. By varying the solvent composition with a combination of tetrahydrofuran and 2-Methyltetrahydrofuran solvents and sodium hexafluorophosphate (NaPF6) salt, the freezing point, solubility, and Na+ solvation structure of the electrolyte is modulated and studied in detail. The extensive anion engagement in the optimized mix solvent electrolyte facilitated the formation of a stable and inorganic-rich solid electrolyte interphase layer, ensuring low overpotentials and uniform Na+ deposition, yielding superior cycling stability. As a result, the developed electrolyte enables SIBs to achieve reversible capacities of 88 mAh g(-1) at -60 degrees C and 50 mAh g(-1) at -100 degrees C. These insights may contribute to developing improved energy storage devices suitable for challenging environmental conditions.
Keywords: contact-ion pair; solid electrolyte interphase (SEI); solvation; ultra-low temperature; XPS-depth Profiling

Facile synthesis of fluoride-free mxene nanosheets as an efficient anode for lithium-ion capacitor - Pawar, Meenakshi D.; Shinde, Dhanraj; Shelke, Manjusha (Chemistry-an Asian Journal, 2026)
MXenes are a promising class of two-dimensional (2D) nanomaterials known for their exceptional metallic conductivity and adjustable surface chemistry. However, the current state-of-the-art synthesis methods rely on the chemical etching of MAX phase (e.g., Ti3AlC2) with HF or fluoride-based compounds, leading to fluorine-terminated MXenes. These MXenes suffer from poor stability in ambient conditions, restricting their applications, particularly in lithium-ion-based batteries and capacitors (LIBs and LICs). In this study, we present a two-step method to produce fluorine-free MXene, addressing the stability issues of MXene in aqueous dispersions and relatively improved performance in LICs. Specifically, an efficient etching process employing hydroiodic acid (HI) with vinegar is used for the selective removal of the A layer from the MAX phase, resulting in F-free exfoliated MXenes (HVM). The HVM shows an outstanding electrical conductivity of 388 S cm(-1), maintaining high stability in aqueous dispersions over two weeks. HVM as electrode shows significantly enhanced Li+ ion storage capabilities, delivering a discharge capacity of 295 mAh g(-1) over 500 cycles at 1 A g(-1), substantially outperforming MXenes derived from F-based etching approaches. Furthermore, the HI-vinegar etching mechanism introduces unique surface functionalities that provide HVM superior cycling stability and rate capability, enabling more stable, high-performance MXene-based energy storage devices.
Keywords: 2D materials; Electrical conductivity; fluoride-free MXene; HVM anode; Lithium-ion capacitor; lithium-ion diffusion

Molecularly engineered PW12@Polypyrrole/MXene composite for high-energy, high-rate lithium-ion capacitor - Pawar, Meenakshi D.; Pandey, Priyanshi; Shelke, Manjusha (Journal of Energy Storage, 2026)
Due to inherent differences in the charge storage mechanisms of anode and cathode in a hybrid lithium-ion capacitor (LIC), a significant kinetic balance exists, necessitating the need to improve the ion/electron transfer capability of anode materials. In this study, we have developed a ternary pseudocapacitive composite comprising redox-active phosphotungstic acid nanoclusters (PW12) anchored to polypyrrole nanofibers (PPy), which are further decorated with Ti3C2Tx MXene (PW12@PPy/Ti3C2Tx) synthesized via an in-situ polymerization strategy. Here, Ti3C2Tx MXene serves as a conductive scaffold for PW12 wrapped PPy nanofibers, promoting efficient electron/ion transport. Simultaneously, the incorporation of PW12-anchored PPy nanofibers effectively mitigates the natural tendency of MXene to restack, thus preserving its layered structure. The PW12@PPy/Ti3C2Tx hybrid composite material delivers a high specific capacity of 767 mAh g-1 at 0.1 A g-1 after 100 cycles and a promising cycling stability of 280 mAh g-1 at 1 A g-1 up to 600 cycles. Moreover, an assembled LIC device using PW12@PPy/Ti3C2Tx as anode with nitrogen-doped sucrose carbon (NSC) as cathode demonstrates the highest energy density of 125 Wh kg-1 and maximum power density of 17,058 W kg-1. The device also maintains good cycling stability of 78.4 % capacity retention after 10,000 cycles at 1 A g-1. These results highlight a promising pathway for designing MXene-based hybrid composites with enhanced lithium storage performance, effectively addressing the kinetic mismatch challenges in LIC anode applications.
Keywords: Full cell device; Li ion diffusion; Lithium-ion capacitor; MXene; polyoxometalates; polypyrrole